2013
DOI: 10.1128/jb.00110-13
|View full text |Cite
|
Sign up to set email alerts
|

DsbA and MgrB Regulate steA Expression through the Two-Component System PhoQ/PhoP in Salmonella enterica

Abstract: SteA is a protein that can be translocated into host cells through the two virulence-related type III secretion systems that are present in Salmonella enterica. We used the T-POP system to carry out general screens for loci that exhibited activation or repression of a steA::lacZ fusion. These screens identified the histidine kinase PhoQ and the response regulator PhoP as positive regulators of steA. Transcription of this gene is 70 dependent, and the promoter of steA contains a PhoP-binding site that mediates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 60 publications
1
11
0
Order By: Relevance
“…This observation may explain why this promoter was not detected in previous global searches for PhoP-regulated genes based on sequence similarities (49). We previously found a similar situation for the promoter of steA (35), a gene encoding another Salmonella T3SS effector, although for steA, the conserved part of the PhoP box was the proximal half (Fig. 6).…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…This observation may explain why this promoter was not detected in previous global searches for PhoP-regulated genes based on sequence similarities (49). We previously found a similar situation for the promoter of steA (35), a gene encoding another Salmonella T3SS effector, although for steA, the conserved part of the PhoP box was the proximal half (Fig. 6).…”
Section: Discussionmentioning
confidence: 62%
“…Finally, we investigated the possibility of a direct interaction of PhoP with the promoter of slrP using a slot blot technique. Phosphorylated His 6 -PhoP was used for these assays together with PCR-amplified fragments derived from the slrP promoter and the promoters of slyB and phoN, which were used as positive and negative controls, respectively (35,44). As seen in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is not uncommon for TCSs to tune expression of genes. For example, in Salmonella enterica, PhoPQ tunes expression of the effector steA during osmotic stress, and PhoBR tunes expression of itself in E. coli according to environmental phosphate concentrations (69,70). If CvsSR tunes expression of hrpRS, then it is conceivable that deletion of cvsS or cvsR may cause only subtle changes T3SS and T3E deployment that do not affect the HR but could still influence pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The gene steA is located outside SPI1 and SPI2, and its low GC content (43%) suggests horizontal acquisition, common in virulence-associated genes. We have previously shown that its expression is transcriptionally controlled by the bacterial redox status in a PhoQ/PhoP-dependent manner [9]. A steA null mutant is three-fold attenuated for BALB/c mice virulence after intraperitoneal infection [7] and SteA seems to be involved in the bacterial persistence during long time infection in 129X1/SvJ mice [10].…”
Section: Introductionmentioning
confidence: 99%